2008
DOI: 10.1186/jbiol98
|View full text |Cite
|
Sign up to set email alerts
|

Bridge helix and trigger loop perturbations generate superactive RNA polymerases

Abstract: B Br ri id dg ge e h he el li ix x a an nd d t tr ri ig gg ge er r l lo oo op p p pe er rt tu ur rb ba at ti io on ns s g ge en ne er ra at te e s su up pe er ra ac ct ti iv ve e R RN NA A p po ol ly ym me er ra as se es s A Ab bs st tr ra ac ct t B Ba ac ck kg gr ro ou un nd d: : Cellular RNA polymerases are highly conserved enzymes that undergo complex conformational changes to coordinate the processing of nucleic acid substrates through the active site. Two domains in particular, the bridge helix and the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
151
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(163 citation statements)
references
References 49 publications
11
151
1
Order By: Relevance
“…4C). These results are consistent with mutagenesis experiments on a related multisubunit RNAP (40), where valine mutants at this position have lower transcription activity compared with phenylalanine and WT (with tyrosine).…”
Section: The Free-energy Landscape Suggests a Single Rate Limiting Stsupporting
confidence: 89%
“…4C). These results are consistent with mutagenesis experiments on a related multisubunit RNAP (40), where valine mutants at this position have lower transcription activity compared with phenylalanine and WT (with tyrosine).…”
Section: The Free-energy Landscape Suggests a Single Rate Limiting Stsupporting
confidence: 89%
“…Substitution of this region in Taq RNAP with the corresponding region from Dra RNAP resulted in a significant increase in the rate of nucleotide addition, especially at low and moderate temperatures. Remarkably, the observed increase was much more dramatic than reported previously for substitutions in TL and BH that stimulated the rate of elongation 2-to 3-fold (10,14). We also showed that substitutions of two individual residues from this region in Taq RNAP, Q1046A and S1074A, increased the rate of catalysis about 3-fold.…”
Section: Discussionsupporting
confidence: 57%
“…Even single amino acid substitutions in the structural elements involved in catalysis dramatically alter the catalytic properties of RNAP (3,9,12,14,17,18). We thus wondered whether the differences in the cold sensitivity of the Taq and Dra enzymes could be conferred by changes of just a few residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This provided us with a powerful tool that is readily accessible to saturation mutagenesis approaches during which we can study protein-protein interactions in an unbiased manner and on a single-residue level. Saturation mutagenesis has given us extensive insight into the protein dynamics accompanying the nucleotide addition cycle catalysed by mjRNAP that structural data have failed to uncover (29,30). Given the success in this system, we recently included the interface of the mjTFIIB linker and mjRNAP into our studies to further investigate the stimulation effect of the linker on mjRNAP activity (26).…”
Section: The Tfiib/rnap Interface: Advantages Of Biochemical Analysismentioning
confidence: 99%